2015
DOI: 10.1002/elsc.201500092
|View full text |Cite
|
Sign up to set email alerts
|

A cold‐adapted leucine dehydrogenase from marine bacterium Alcanivorax dieselolei: Characterization and l‐tert‐leucine production

Abstract: l‐tert‐leucine, an intermediate in the synthesis of several chiral drugs, is mainly produced by bioconversion, in which leucine dehydrogenase (LeuDH) is the key enzyme. A novel leudh was obtained from the marine bacterium Alcanivorax dieselolei B‐5(T) by PCR. The gene encoded a novel cold‐adapted LeuDH that showed low similarity (less than 50%) to any known proteins; the highest similarity (42.6%) was found for LeuDH from Bacillus cereus. The cold‐adapted LeuDH showed optimal activity at 30℃ and pH 6.5, and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…A extremophilic leucine dehydrogenase gene from Alcanivorax dieselolei B-5(T) (Marine Culture Collection of China 1A02288) isolated from surface seawater at Bohai Sea (China) (Liu and Shao, 2005) was cloned and expressed in E. coli , presenting a specific activity of 0.88 U/mg and affinity to catalyze reactions in cold temperatures, 0–37°C (Figure 15A). Trimethylpyruvic acid was employed as substrate and the leucine dehydrogenase enzyme produced L - tert -leucine, which is an important construction block for chiral drugs (Jiang et al, 2016).…”
Section: Isolated Enzymesmentioning
confidence: 99%
“…A extremophilic leucine dehydrogenase gene from Alcanivorax dieselolei B-5(T) (Marine Culture Collection of China 1A02288) isolated from surface seawater at Bohai Sea (China) (Liu and Shao, 2005) was cloned and expressed in E. coli , presenting a specific activity of 0.88 U/mg and affinity to catalyze reactions in cold temperatures, 0–37°C (Figure 15A). Trimethylpyruvic acid was employed as substrate and the leucine dehydrogenase enzyme produced L - tert -leucine, which is an important construction block for chiral drugs (Jiang et al, 2016).…”
Section: Isolated Enzymesmentioning
confidence: 99%
“…The temperature characteristic of rPsLeuDH was shown in Figure 4 a. It exhibited the highest activity at 30 °C, and that of a cold-adapted LeuDH was 30 °C [ 12 ], whereas thermophilic LeuDH was approximately 40–65 °C [ 6 , 22 ], or (60–75 °C) [ 5 ]. It is worth pointing out that rPsLeuDH retained 40% of the highest activity at 0 °C, suggested that the enzyme is a cold-adapted enzyme [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was stable and retained 85% of its initial activity after incubating at 30 °C after 120 min. While, after incubating at 50 °C for 20 min, it was only 30% of its activity lower than other cold-adapted LeuDHs from Alcanivorax dieselolei [ 12 ] and Sporosarcina psychrophila [ 7 ]. However, thermostable LeuDH could retain full activity after incubation at 65 °C for 10 min [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum temperature of EsiLeuDH was 40 • C, and the enzyme activity decreased rapidly when the temperature exceeded 60 • C (Figure 4A). Jiang have shown that the optimum temperature of LeuDH from Alcanivorax dieselolei was 30 • C (Zhu et al, 2016), but Zhu indicated that the value increased to 60 • C when LeuDH from Laceyella sacchari was investigated (Jiang et al, 2016), suggesting significant differences in the catalystic properties of this enzyme from different species. Another important parameter for the purified EsiLeuDH is the optimal pH, which was determined as shown in Figure 4B.…”
Section: Enzyme Cloning Expression and Purificationmentioning
confidence: 99%